Active and healthy lifestyle in Brazilian Primary Health Care user’s: A pragmatic clinical trial about "VAMOS" behavior change program (Research, Society and Development, 2021)
This study aimed to investigate the effectiveness and maintenance of the behavior change program "VAMOS", version 2.0, on behavioral and health outcomes in Brazilian users (≥ 18 years) of Primary Health Care (PHC) in Florianópolis, state of Santa Catarina, southern Brazil. A pragmatic clinical trial was carried out between 2016 and 2019 in Basic Health Units, with 265 users allocated in the intervention group (n = 125) and the control group (n = 140). The intervention group participated for three months in the VAMOS to promote physical activity (PA) and a healthy diet. The control group received in a single meeting counseling about the importance of an active and healthy lifestyle. Variables of PA (daily minutes in light PA, moderate-to-vigorous PA, total PA, and sedentary behavior), eating behavior (weekly consumption of fruits, vegetables, and soda drinks), anthropometry (body mass, waist circumference (WC), and body mass index), and quality of life (QOL) (positive or negative perception), were evaluated, through interviews and objective measures, in the pre-intervention, post-intervention, and 12 months after the end of the intervention. The intervention group increased moderate-to-vigorous PA bouts, consumed of vegetables and, QOL, and decreased the consumption of soda drinks and WC (p